Giant negative thermal expansion in Zn2-xCuxP2O7 ceramics via microstructure effect. Issue 1 (1st January 2023) - Shi, Naike; Song, Yuzhu; Zhou, Chang; Fan, Longlong; Chen, Jun
Abstract: As a novel thermophysical behavior, negative thermal expansion (NTE) has been studied in many materials. However, rare materials have realized giant NTE, and the methods to improve NTE are lacking. Herein, a giant NTE has been achieved in Zn2- x Cu x P2 O7 ceramics via microstructure effect. In the Zn1.96 Cu0.04 P2 O7 ceramic body, the linear contraction measured by dilatometry reaches to 0.9% (3ΔL/L = 2.7%) when heated from −30 °C to 125 °C, while the intrinsic crystallographic volume contraction derived by X-ray diffraction is only 1.68%. The remarkable NTE enhancement in the ceramic sample is attributed to the microstructure effect. An apparent shrinkage of the voids has been observed by in-situ atomic force microscope (AFM). The voids with large size in the ceramic body is the key factor to enhance NTE. This is the first time to observe direct experimental evidence by AFM for microstructure effect. Microstructure effect is an effective method to produce giant NTE.